Targeting Head and Neck Cancer by Vaccination - Wang, Chuan; Dickie, James; Sutavani, Ruhcha V.; Pointer, Catherine; Thomas, Gareth J.; Savelyeva, Natalia (Frontiers in Immunology, 2018)
Head and neck cancer (HNC) is a heterogeneous group of squamous cell cancers that affect the oral cavity, pharynx, and larynx. Worldwide, it is the sixth most common cancer but in parts of Southern and South-East Asia, HNC is one of the most common cancers. A significant proportion of HNC is driven by human papillomavirus (HPV) infection, whereas HPV-independent HNC is associated with alcohol, smoking, and smokeless tobacco consumption. Here, we review the past and present experience of targeting HNC with vaccination focusing on HPV-derived antigens as well as non-viral antigens for HPV-negative HNC. Novel therapeutic approaches for HNC will focus not only on effective vaccine platforms but will also target the stroma-rich immunosuppressive microenvironment found in those tumours.